The power of corporate communication : crafting the voice and image of your business - Argenti, Paul A.; Forman, Janis (New York : McGraw-Hill, 2002)
Effective corporate communication requires a carefully formulated and implemented program, one that will both craft your corporation's image and protect that image when problems arise. This is a guide for mastering the art - and leveraging the power - of corporate communication.
Includes bibliographical references (p. 267-282) and index.
Keywords: Communication in management; Corporations -- Public relations; Communication in organizations